Stability of Traveling Waves to the Lotka-Volterra Competition Model - Ahmad Alhasanat; Chunhua Ou (Complexity)
In this paper, the stability of traveling wave solutions to the Lotka-Volterra diffusive model is investigated. First, we convert the model into a cooperative system by a special transformation. The local and the global stability of the traveling wavefronts are studied in a weighted functional space. For the global stability, comparison principle together with the squeezing technique is applied to derive the main results.